Selection for Biomass Yield in Upland, Lowland, and Hybrid Switchgrass. Issue 2 (1st March 2014) - Casler, Michael D.; Vogel, Kenneth P.
ABSTRACT: Switchgrass ( Panicum virgatum L.) is a candidate for cellulosic bioenergy feedstock development in many parts of North America, Europe, and Asia. Breeding for increased biomass yield is a viable and desirable research objective to improve both economic and energy yields per hectare. The objectives of this study were to estimate progress from (i) selection for biomass yield in upland switchgrass, (ii) selection for winter survival, biomass yield, and biomass quality in lowland switchgrass, and (iii) advanced‐generation heterosis effects in four upland × lowland hybrid switchgrass populations. Selection for increased biomass yield in upland switchgrass resulted in mean genetic gains for of 0.71 Mg ha −1 per cycle (8% per cycle = 4% yr −1 ) for biomass yield. Selection for increased biomass yield in lowland switchgrass resulted in mean genetic gains of 0.89 Mg ha −1 (18% = 1% yr −1 ) for biomass yield. Mean high‐parent heterosis between upland and lowland ecotypes was 3.57 Mg ha −1 (43%). These gains in biomass yield resulted in significant increases in ethanol production for a fermentation platform or high heating value for a combustion platform. Biomass yield is a moderately heritable trait in switchgrass and it can be readily improved in both upland and lowland populations using conventional breeding methods.